2008
DOI: 10.1175/2007jpo3682.1
|View full text |Cite
|
Sign up to set email alerts
|

Wave-Coherent Air–Sea Heat Flux

Abstract: Air-sea fluxes of heat and momentum play a crucial role in weather, climate, and the coupled general circulation of the oceans and atmosphere. Much progress has been made to quantify momentum transfer from the atmosphere to the ocean for a wide range of wind and wave conditions. Yet, despite the fact that global heat budgets are now at the forefront of current research in atmospheric, oceanographic, and climate problems and despite the good research progress in recent years, much remains to be done to better u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
32
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 47 publications
(35 citation statements)
references
References 35 publications
3
32
0
Order By: Relevance
“…In addition to the stress from the viscous boundary effects and turbulence, there is also stress due to the form of the waves (e.g., Janssen, 1989;Belcher and Hunt, 1993;Makin et al, 1995;Hare et al, 1997;Edson and Fairall, 1998). Recent work (Veron et al, 2008) at low to moderate wind speeds has also shown that that there are wave-modulated sensible and latent heat fluxes. In the marine atmospheric boundary layer, the partition between viscous, turbulent, and wave stresses, is poorly understood.…”
Section: Air-sea Momentum Transfer and Ocean Wavesmentioning
confidence: 99%
“…In addition to the stress from the viscous boundary effects and turbulence, there is also stress due to the form of the waves (e.g., Janssen, 1989;Belcher and Hunt, 1993;Makin et al, 1995;Hare et al, 1997;Edson and Fairall, 1998). Recent work (Veron et al, 2008) at low to moderate wind speeds has also shown that that there are wave-modulated sensible and latent heat fluxes. In the marine atmospheric boundary layer, the partition between viscous, turbulent, and wave stresses, is poorly understood.…”
Section: Air-sea Momentum Transfer and Ocean Wavesmentioning
confidence: 99%
“…The understanding of dissipation induced by breaking waves at various scales has been the topic of intensive research in recent decades, combining field work in the open ocean (Melville 1996;Melville & Matusov 2002;Veron et al 2008;Sutherland & Melville 2013), laboratory experiments on wave breaking (Melville & Rapp 1985;Tulin & Waseda 1999;Rapp & Melville 1990;Banner & Peirson 2007;Drazen et al 2008), and the dissipation induced by smaller scales involving surface tension, like micro-breaking, spilling breaking (Duncan et al 1999;Duncan 2001;Liu & Duncan 2003, 2006 and parasitic capillary waves (Perlin et al 1993;Jiang et al 1999;Caulliez et al 1998;Su 1982;Caulliez 2013). The importance of small scales, O(1 − 10) cm in the global ocean wave energy fluxes is still an open question and needs further investigation.…”
Section: Introductionmentioning
confidence: 99%
“…(Lumley and Terray 1983;Thais and Magnaudet 1996;Hristov et al 1998;Veron et al 2008;Grare et al 2013a). This is in part due to the technical difficulty associated with making measurements close to the air water interface in the laboratory or the field, and the difficulty in modeling the complex non-linear interactions between the turbulence and the surface waves.…”
Section: Introductionmentioning
confidence: 99%